Carboxypeptidase A1 (CPA1) Immunohistochemistry Is Highly Sensitive and Specific for Acinar Cell Carcinoma (ACC) of the Pancreas. (January 2022) - Uhlig, Ria; Contreras, Hendrina; Weidemann, Sören; Gorbokon, Natalia; Menz, Anne; Büscheck, Franziska; Luebke, Andreas M.; Kluth, Martina; Hube-Magg, Claudia; Hinsch, Andrea; Höflmayer, Doris; Fraune, Christoph; et al.
Abstract : Carboxypeptidase A1 (CPA1) is a zinc metalloprotease that is produced in pancreatic acinar cells and plays a role in cleaving C-terminal branched-chain and aromatic amino acids from dietary proteins. This study assessed the utility of immunohistochemical CPA1 staining for diagnosing pancreatic acinar cell carcinoma (ACC). A total of 12, 274 tumor samples from 132 different tumor types and subtypes as well as 8 samples each of 76 different normal tissue types were interpretable by immunohistochemistry in a tissue microarray format. CPA1 was strongly expressed in acinar cells of all normal pancreas samples but not in any other normal tissues. CPA1 immunostaining was detected in 100% of 11 pancreatic ACCs and 1 mixed acinar endocrine carcinoma, but absent in 449 pancreatic ductal adenocarcinomas, 75 adenocarcinomas of the ampulla Vateri, and 11, 739 other evaluable cancers from 128 different tumor entities. A weak to moderate diffuse staining of epithelial and stromal cells of cancer tissues immediately adjacent to non-neoplastic pancreatic acinar cells often occurred and was considered to be caused by the diffusion of the highly abundant CPA1 from normal acinar cells that may have suffered some autolytic cell damage. In conclusion, our data show that CPA1 is a highly sensitive and largely specific marker for normal and neoplastic pancreatic acinar cells. CPA1 immunohistochemistry greatly facilitates the otherwise often difficult diagnosis of pancreatic ACC.